Acute Cognitive and Physical Rest May Not Improve Concussion Recovery Time. Issue 4 (July 2016) - Buckley, Thomas A.; Munkasy, Barry A.; Clouse, Brandy P.
Abstract : Objective: To evaluate the effectiveness of an acute period of cognitive and physical rest on concussion. Participants: Fifty consecutive patients with a diagnosis of concussions. Design: Participants were evaluated before ( n = 25) and after ( n = 25) a policy change that incorporated cognitive and physical rest. Patients in the rest group were withheld from activities, including classes, for the remainder of the injury day and the following day, whereas patients in the no-rest group were not provided any postinjury accommodations. Main Measures: Patients were evaluated on a graded symptom checklist, Balance Error Scoring System, Standard Assessment of Concussion, and computerized neuropsychological tests. The number of days until each test achieved baseline values was compared between groups with independent-samples t test. Results: The no-rest group achieved asymptomatic status sooner than the rest group (5.2 ± 2.9 days and 3.9 ± 1.9 days, respectively; P = .047). There were no differences between groups for time to baseline values on the Balance Error Scoring System, Standard Assessment of Concussion, computerized neuropsychological tests, or time to clinical recovery. Conclusion: A prescribed day of cognitive and physical rest was not effective in reducing postconcussion recovery time. These results agree with a previous study and suggest that light activity postconcussion may not be deleterious to the concussion recovery process.